Analisis Gaya Kepimpinan dalam Meningkatkan Kinerja Pegawai pada Dinas Energi dan Sumber Daya Mineral Provinsi Jawa Timur - Aulia Rahel; Suryanto Suryanto (Universitas Batanghari Jambi, 2023)
The Office of Energy and Human Resources of East Java Province is a Regional Apparatus in charge of regional government affairs in the field of energy and mineral resources. Problems arise from the leadership style in the Department of Energy and Mineral Resources of East Java Province which is too rigid and often does not listen to input from employees so that it has an impact on employee performance. The type of research used in terms of the location of the data source includes case research and field research. This research approach uses descriptive qualitative. The research was conducted at the Office of Energy and Mineral Resources of East Java Province with data collection techniques in the form of interviews. The results of the study show that the leadership style in the Energy and Mineral Resources Office of East Java Province applies a mixed leadership style, namely an autocratic and participative style. This is assessed from several indicators such as: delegating authority, ability to make decisions, the nature of the leader, the ability to control and control subordinates.